A Fair Exchange: The Reciprocal Relationship Between Universities and Clinical Placement Supervisors - Sheils, Elizabeth A.; Loades, Maria E.; Medley, Andrew R.; Marks, Elizabeth M. (International Journal of Practice-based Learning in Health and Social Care, 2016)
Clinical psychology training in the UK relies heavily upon supervised clinical practice placements. Placement supervisors have a significant responsibility for providing trainees with the learning experiences required for qualification. The role is demanding and whilst the university benefits greatly, it is less clear what supervisors receive in return. This is important when one considers how positive relationships and social action are influenced by reciprocity and a sense of belongingness. Despite its importance, no research has directly explored the relationship between supervisors and the university in a clinical psychology training context. This novel study sought to explore how supervisors perceive their role and their connectedness / belongingness to the university, and whether technology utilized by other areas of pedagogy led to improvements. Access to electronic resources was sent to clinical placement supervisors (n=100). A subset of these (n=7) signed up to complete a semi-structured interview. The interviews were analysed using template analysis. Common themes emerged, including perceived benefits of the supervisor role, such as feeling connected to the training course, despite significant challenges and demands. The provision of electronic resources was found to have the potential to enhance connectedness for all stakeholders. The implications of these findings are discussed.